2015
DOI: 10.1007/s13593-015-0333-y
|View full text |Cite
|
Sign up to set email alerts
|

The blurred boundaries of ecological, sustainable, and agroecological intensification: a review

Abstract: The projected human population of nine billion by 2050 has led to ever growing discussion of the need for increasing agricultural output to meet estimated food demands, while mitigating environmental costs. Many stakeholders in agricultural circles are calling for the intensification of agriculture to meet these demands. However, it is neither clear nor readily agreed upon what is meant by intensification. Here, we compare the three major uses, 'ecological intensification', 'sustainable intensification' and 'a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(112 citation statements)
references
References 53 publications
1
93
0
4
Order By: Relevance
“…These observations brought the authors to suggest "ecological intensification" as an alternative concept. Wezel et al (2015) identified three major concepts of intensification, i.e. sustainable intensification, ecological intensification, and agroecological intensification, but noted that all three concepts are actually poorly or imprecisely defined, often misused, or unclear in their practical implications.…”
Section: Sustainable Intensificationmentioning
confidence: 99%
See 3 more Smart Citations
“…These observations brought the authors to suggest "ecological intensification" as an alternative concept. Wezel et al (2015) identified three major concepts of intensification, i.e. sustainable intensification, ecological intensification, and agroecological intensification, but noted that all three concepts are actually poorly or imprecisely defined, often misused, or unclear in their practical implications.…”
Section: Sustainable Intensificationmentioning
confidence: 99%
“…This definition restricts sustainability to very specific types of inputs and resources. Wezel et al (2015) referred to a recent and widely cited definition of sustainable intensification by FAO (2011b): "producing more from the same area of land while conserving resources, reducing negative impacts on the environment and enhancing natural capital and the flow of ecosystem services". This link with ecosystem services brings the definition much closer to that of ecological intensification (see below).…”
Section: Sustainable Intensificationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the more ecologically based systems have also expanded in the last decades: organic agriculture has been gaining popularity all over the world and traditional family farming, mainly in the tropics and subtropics, is still the backbone of world food production. Moreover, within classical conventional agriculture, ecological elements and the better use of ecological processes are proposed more and more often under the paradigm of sustainable or ecological intensification (Wezel et al 2015).…”
Section: Introductionmentioning
confidence: 99%